Corporate Social Responsibility and Bank’s Performance under the Mediating Role of Customer Satisfaction and Bank Reputation - Kim Quoc Trung Nguyen (Emerging Science Journal, 2022)
This paper aims to examine the indirect linkage between corporate social responsibility (CSR) and firm performance via the effects of customer satisfaction and bank reputation. The study applies Structural Equation Modelling (SEM) to a sample of top managers, finance managers, chief accountants, and employees in Vietnamese state-owned commercial banks. The findings explore the statistically significant effect of CSR on bank performance under the mediating role of customer satisfaction and bank reputation, which are not concerned by previous studies. Because CSR activities assist banks in maintaining their reputation by complying with a long-term commitment to stakeholders' interests and providing valuable customer benefits to increase their satisfaction. So, the research results show that customer satisfaction and the bank's reputation promote a positive relationship between CSR and bank performance. Doi: 10.28991/ESJ-2022-06-06-012 Full Text: PDF